(untitled) (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2024)
Managing traffic is one of the critical assignments of the police officers of PNP. There are instances that they encounter a situation where their capabilities as traffic police can be put to the test. As traffic police, they are responsible for ensuring the safety of road users and pedestrians, monitoring the traffic to identify road users who disobey traffic laws, and issuing tickets as penalties. Also, they are the ones who first respond if there is an accident. Part of their job as first respondents in traffic accidents are giving first aid to injured road accident victims, searching for injured people to bring them to the hospital immediately, and taking pictures for documentation. It is not possible to prevent problems regarding traffic like vehicular accidents, but with the help of knowledgeable, alert, and skilled traffic police, the severity of injuries can be prevented or minimized. It was discovered that respondents assessed the capabilities of traffic police based on their knowledge of how to use different traffic equipment, how traffic police conducted initial accident assessment upon responding to traffic accidents, and their skills on how they were able to coordinate multiple vehicles and prioritized the smooth flow of traffic. There were many factors that affected the capabilities of police officers in handling traffic, such as the behavior of road users, weather, technologies, and equipment of traffic police, the area where they are assigned, and their health condition. For further enhancement of the capabilities of police officers in implementing traffic rules and regulations, the government should provide seminars to traffic police in order to enhance their capabilities about traffic rules and regulations, upgrade their technologies and equipment, and enforce strict traffic laws.